Análisis del papel que juega la radio y la televisión de la ciudad de Loja, en la información acerca de las semillas transgénicas y de la soberanía alimentaria, durante el segundo semestre del año 2015. - Rios Elizalde, Tatiana Yamilet (2017)
This is an investigation that is based on analyzing the role played by the media in the city of Loja on information and campaigns transgenic seeds. For this he turned to the field research and the application of techniques and methods to reach final conclusions. Five means of communication in order to know if socialize met the above information, nearing the end of the investigation to the conclusion that the issue is not addressed in any of the means that exist in the town were studied. Action is worrying, because they are taking new measures in the country, because it is making the change of productive matrix and society has a right to know this information that somehow will change the production processes at the national level . That is why at the end of the investigation has proceeded to make an alternative proposal to be integrated into the programming grids of the media of the city so that it can inform and socialize issues of concern affecting all Ecuadorians